Preoperative FDG-PET/CT Is an Important Tool in the Management of Patients with Thick (T4) Melanoma - Rodrigo Arrangoiz; Pavlos Papavasiliou; Carrie A. Stransky; Jian Q. Yu; Li Tianyu; Elin R. Sigurdson; Adam C. Berger; Jeffrey M. Farma (Hindawi Limited, 2012)
The yield of preoperative PET/CT (PET/CT) for regional and distant metastases for thin/intermediate thickness melanoma is low. Objective of this study is to determine if PET/CT performed for T4 melanomas helps guide management and alter treatment plans. Methods. Retrospective cohort of 216 patients with T4 melanomas treated at two tertiary institutions. Fifty-six patients met our inclusion criteria (T4 lesion, PET/CT and no clinical evidence of metastatic disease). Results. Fifty-six patients (M: 32, F: 24) with median tumor thickness of 6 mm were identified. PET/CT recognized twelve with regional and four patients with metastatic disease. Melanoma-related treatment plan was altered in 11% of the cases based on PET/CT findings. PET/CT was negative 60% of the time, in 35% of the cases; it identified incidental findings that required further evaluation. Conclusion. Patients with T4 lesions, PET/CT changed the treatment plan 18% of the time. Regional findings changed the surgical treatment plan in 11% and the adjuvant plan in 7% of our cases due to the finding of metastatic disease. Additionally 20 patients had incidental findings that required further workup. In this subset of patients, we feel there is a benefit to PET/CT, and further studies should be performed to validate our findings.